Why the WTO? An Introduction to the Economics of Trade Agreements - Gene M. Grossman; Henrik Horn (Research Institute of Industrial Economics (IFN), 2012)
This study is part of The American Law Institute (ALI) project Legal and Economic Principles of World Trade Law. The project aims to analyze the central instrument in the World Trade Organization (WTO) Agreement for the regulation of trade in goods The General Agreement on Tariffs and Trade GATT). The present study is one of two background studies for this project*. The first study, The Genesis of the GATT, appraises the rationale for the creation of the GATT, and tracks its development from a historical and legal perspective. This second study provides an overview of the economics of trade agreements. * There is a second leg to the ALI project, in which economists and lawyers jointly analyze the emerging case law from the WTO dispute-settlement mechanism.
Keywords: F13; 330; Trade agreements; GATT; WTO; WTO-Regeln; Handelsabkommen; Außenwirtschaftsrecht